2021
DOI: 10.3389/fmicb.2021.584850
|View full text |Cite
|
Sign up to set email alerts
|

Highly Contaminated Marine Sediments Can Host Rare Bacterial Taxa Potentially Useful for Bioremediation

Abstract: Coastal areas impacted by high anthropogenic pressures typically display sediment contamination by polycyclic aromatic hydrocarbons (PAHs) and heavy metals (HMs). Microbial-based bioremediation represents a promising strategy for sediment reclamation, yet it frequently fails due to poor knowledge of the diversity and dynamics of the autochthonous microbial assemblages and to the inhibition of the target microbes in the contaminated matrix. In the present study, we used an integrated approach including a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 87 publications
(113 reference statements)
1
26
0
Order By: Relevance
“…However, the scarcity of indigenous microbes with the proper metabolic predispositions to degrade petroleum hydrocarbons, could represent a limitation of this approach [9]. Bioaugmentation, through the addition of microorganisms with biodegradation/detoxification capacity [10] such as specific oil-degrading bacteria that could be previously isolated from a contaminated (or pre-contaminated) site, could be an option. The success of biotechnological solutions for bioremediation application depends on the identification and selection of the indigenous hydrocarbon-degrading microbial assemblages from a target contaminated environment and enhance their biodegradation potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the scarcity of indigenous microbes with the proper metabolic predispositions to degrade petroleum hydrocarbons, could represent a limitation of this approach [9]. Bioaugmentation, through the addition of microorganisms with biodegradation/detoxification capacity [10] such as specific oil-degrading bacteria that could be previously isolated from a contaminated (or pre-contaminated) site, could be an option. The success of biotechnological solutions for bioremediation application depends on the identification and selection of the indigenous hydrocarbon-degrading microbial assemblages from a target contaminated environment and enhance their biodegradation potential.…”
Section: Introductionmentioning
confidence: 99%
“…The success of biotechnological solutions for bioremediation application depends on the identification and selection of the indigenous hydrocarbon-degrading microbial assemblages from a target contaminated environment and enhance their biodegradation potential. At the same time, the optimization of the lab-grown condition of the bacterial strains selected are needed to improve the efficiency of bioaugmentation approaches and bioremediation performance [10][11][12][13][14]. Therefore, even though bioremediation is seen as an efficient tool for removing pollutants, investigation in this field is still required to expand knowledge regarding microorganisms, native to different environmental niches, with a good remediation capacity and adaptability.…”
Section: Introductionmentioning
confidence: 99%
“…In order to gain insight into potential functional patterns, clusters’ distinctive metabolic pathways were highlighted as studies have demonstrated how changes in environmental factors influence the phylogenetic diversity and functional traits of the microbial communities, and consequently ecosystem function ( Baltar et al, 2016 ; Lucas, Wichels & Gerdts, 2016 ; Thompson et al, 2017 ; Tinta et al, 2015 ; Zhang, Zheng & Jiao, 2016 ). The Southern GoM continental slope (cluster I) is considered to be impacted by high anthropogenic pressures, specially from the oil industry and river run off, and typically display sediment contamination by polycyclic aromatic hydrocarbons and heavy metals, which in turn can result in oxidative stress with cascade effects on the marine ecosystem ( Dell’Anno et al, 2021 ). The Entner- Doudoroff (ED) pathway was observed as one of the potential routes in the cycling of mono- and polysaccharides at the continental slope (cluster I) deep-sediments.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread contamination of marine systems by hydrocarbons, especially in coastal areas characterized by high anthropogenic pressure, has stimulated research focused on the identification of the bacterial taxa most effective in their removal [ 99 ]. The bacteria most often associated with the presence of oil in the sea include those belonging to the gammaproteobacteria, especially members of Oceanospirillales and Alteromonadales [ 20 , 24 ], including hydrocarbon degraders ( Table 2 ), such as Alcanivorax , Halomonas , Marinobacter , Oleispira , Thalassolituus , and Oleiphilus .…”
Section: Bacterial-mediated Degradation Of Petroleum Hydrocarbonsmentioning
confidence: 99%
“…Microbial taxa potentially beneficial for the bioremediation of contaminated sediments can be originally from the same area, or can be isolated from other contaminated areas [ 19 , 20 ]. The use of autochthonous microorganisms is expected to be more effective and ecologically friendly, since these are likely better adapted to the specific local environmental conditions than allochthonous microbes, which may require the manipulation of the natural environment to maximize their performance (e.g., changing oxygen and/or nutrient concentration, pH [ 21 ]).…”
Section: Introductionmentioning
confidence: 99%